MicroRNAs and human cancer - Nikitina, E.G.; Urazova, L.N.; Stegny, V.N. (Experimental Oncology, 2012)
MicroRNAs (miRNAs) are a recently discovered family of short non-coding RNA molecules of about 19–24 nucleotides in length that are involved in regulation of gene expression. These small molecules have been found to regulate genes involved in diverse biological processes such as cell proliferation, development, differentiation, apoptosis and others. MiRNAs regulate gene expression at the post-transcriptional level either by inhibition of the target (mRNA) or by its destruction. Recent studies have shown that mRNA deregulation is a basic problem in studying pathogenesis of many malignant tumors. It has been recently shown that miRNAs are able to regulate thousands of target genes simultaneously. Thus, the key role of miRNA in carcinogenesis reveals a new layer in the molecular architecture of cancer. Patterns of altered miRNA expression in cancer may serve as molecular biomarkers for tumor diagnosis, prognosis of disease-specific outcomes, and prediction of therapeutic responses. Furthermore, miRNAs may serve as specific targets of new gene therapies.